Freeway Traffic Modelling and Control - Ferrara, Antonella; Sacone, Simona; Siri, Silvia (Advances in Industrial Control, 2018)
This monograph provides an extended overview of modelling and control approaches for freeway traffic systems, moving from the early methods to the most recent scientific results and field implementations. The concepts of green traffic systems and smart mobility are addressed in the book, since a modern freeway traffic management system should be designed to be sustainable. Future perspectives on freeway traffic control are also analysed and discussed with reference to the most recent technological advancements The most widespread modelling and control techniques for freeway traffic systems are treated with mathematical rigour, but also discussed with reference to their performance assessment and to the expected impact of their practical usage in real traffic systems. In order to make the book accessible to readers of different backgrounds, some fundamental aspects of traffic theory as well as some basic control concepts, useful for better understanding the addressed topics,are provided in the book. This monograph can be used as a textbook for courses on transport engineering, traffic management and control. It is also addressed to experts working in traffic monitoring and control areas and to researchers, technicians and practitioners of both transportation and control engineering. The authors' systematic vision of traffic modelling and control methods developed over decades makes the book a valuable survey resource for freeway traffic managers, freeway stakeholders and transportation public authorities with professional interests in freeway traffic systems. Advances in Industrial Control reports and encourages the transfer of technology in control engineering. The rapid development of control technology has an impact on all areas of the control discipline. The series offers an opportunity for researchers to present an extended exposition of new work in all aspects of industrial control. .